"The school where I am educated and which I love so much": analyzing the school archive of the Escuela Superior de Niñas nº 2 (Resistencia, Chaco), from an archival perspective (Praxis Educativa, 2022)
The purpose of this article is to identify the ways in which the Escuela Superior de Niñas nº 2 (located at the Resistencia city, Chaco province, Argentine) and the daily life of the school are represented, based on the written reports of its students about a specific event: the fiftieth anniversary of the school in 1938. The theoretical-methodological support of this research is based on the foucauldian perspectives on discourse analysis and archival theory, which allow us to establish dialogues around the historical and political conjunctures of the time. Considering the conceptions around the school, pedagogical and academic discourse, it was possible to identify that these discourses are supported by discursive formations that provide the basis for different interpretations about the daily school life, the importance of that school for the society from Resistencia and its value for the economic growth of Chaco, in the historical-political conjuncture of the time.
Keywords: school archive; elementary school; school discourse; pedagogical discourse; academic discourse